Синтез та антибактеріальна активність в ряду нових S-похідних (1,2,4-триазол-3(2H)-іл)метил)тіопіримідинів - Карпенко, Юрій Вікторович; Панасенко, Олександр Іванович; Сирота, П. С.; Karpenko, Y. V.; Panasenko, O. I.; Syrota, P. S. (My University, 2023)
Вступ. Актуальність дослідження похідних 1,2,4‐триазолу з піримідиновим фрагментом обумовлена синтезом потенційних антибактерільних лікарських препаратів широкого спектру дії, низькомолекулярних індукторів інтерферону та протипухлинних агентів, пошуком молекулярних дескрипторів їх структури, важливих для встановлення закономірностей «структура – біологічна активність». Мета роботи – комп’ютерний пошук антибактеріальної дії нових гібридів 1,2,4‐триазол‐3(2Н)‐ тіолів з піримідиновим фрагментом щодо 4 тест‐культур, встановити залежність «структура‐дія». Матеріали та методи. Для дослідження сполук використано сучасний комплекс фізико‐хімічних методів дослідження. Для поглибленого вивчення антибактеріальної дії похідних гібридів 1,2,4‐триазол‐ 3(2Н)‐тіолу з піримідиновим фрагментом відібрали 3 тест‐культури музейних штамів грампозитивних і грамнегативних бактерій. Результати. Похідні гібридів 1,2,4‐триазол‐3(2Н)‐тіолу з піримідиновим фрагментом показали високу антибактеріальну активність, щодо грамнегативних мікроорганізмів (E. сoli, Рs. aeruginosa). Отримані експериментальні результати дозволили встановити не тільки роль основних структурних особливостей сполук у прояві антимікробних властивостей. Значною антибактеріальною активністю відрізняються 2‐(((5‐(децилтіо)‐4‐метил‐4Н‐1,2,4‐тріазол‐3‐іл)метил)тіо)піримідин, який блокує ріст E. coli 125 мкг/мл і S. aureus за 125 мкг/мл відповідно. Також варто відзначити похідні 1,2,4‐триазолу, що є активними проти E. coli та S. aureus. The relevance of the study of 1,2,4‐triazole derivatives with a pyrimidine fragment is due to the synthesis of available broad‐spectrum antibacterial drugs, low‐molecular‐weight interferon inducers and antitumor agents, the search for molecular descriptors of their structure, which are important for establishing the "structurebiological activity" laws. The purpose of the work is computer search of the antibacterial action of new hybrids of 1,2,4‐triazole‐3(2H)‐ thiols with a pyrimidine fragment in relation to 4 test cultures, to establish the "structure‐activity" relationship. Materials and methods. A modern set of physico‐chemical research methods was used to study the compounds. For an in‐depth study of the antibacterial effect of hybrid derivatives of 1,2,4‐triazole‐3(2H)‐thiol with a pyrimidine fragment, 3 test cultures of museum strains of gram‐positive and gram‐negative bacteria were selected. The results. Derivatives of 1,2,4‐triazole‐3(2H)‐thiol hybrids with a pyrimidine fragment showed high antibacterial activity against gram‐negative microorganisms (E. soli, Ps. aeruginosa). The obtained experimental results made it possible to establish not only the role of the main structural features of compounds in the manifestation of antimicrobial properties. Significant antibacterial activity is distinguished by 2‐(((5‐(decylthio)‐4‐methyl‐4H‐1,2,4‐ triazol‐3‐yl)methyl)thio)pyrimidine, which blocks the growth of E. coli 125 μg/ml and S. aureus at 125 μg/ml, respectively. It is also worth noting the derivatives of 1,2,4‐triazole, which are active against E. coli and S. aureus.
Synthesis and antibacterial activity of a number of new s‐derivatives (1,2,4‐triazol‐3(2H)‐yl)methyl)thiopyrimidines
Keywords: 1,2,4‐триазол; піримідин; антибактеріальна активність; E. coli, S. aureus; 1,2,4‐triazole; pyrimidine; antibacterial activity; E. coli, S. aureus